2021
DOI: 10.1007/978-3-030-64217-4_31
|View full text |Cite
|
Sign up to set email alerts
|

The Impacts of Climate Zone, Wall Insulation, and Window Types on Building Energy Performance

Abstract: Building energy consumption tends to increase over the next few decades due to the increasing level of urbanization and population. These days much attention has been paid to the enhancement of energy performance of residential and non-residential structures. One should consider various factors for proper building thermal design and assessment. In this study, a simulationbased investigation is applied to analyze the influence of building envelope, climate region, and window's physical features on energy perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…To create a building that meets "green" criteria throughout its lifecycle is a complex task. To solve such a problem, it is necessary to perform a complex of theoretical and field studies [16,17,18,19,20,21,22,23,24,25]. Within the framework of the theoretical part, it is necessary to perform a theoretical justification and selection of the optimal system of criteria for determining the rating in the certification system, indicating that the building meets the "green" category.…”
Section: Discussionmentioning
confidence: 99%
“…To create a building that meets "green" criteria throughout its lifecycle is a complex task. To solve such a problem, it is necessary to perform a complex of theoretical and field studies [16,17,18,19,20,21,22,23,24,25]. Within the framework of the theoretical part, it is necessary to perform a theoretical justification and selection of the optimal system of criteria for determining the rating in the certification system, indicating that the building meets the "green" category.…”
Section: Discussionmentioning
confidence: 99%
“…All of the materials' prices were taken as standard values inserted in the software. The authors of the research have previously used various simulation tools to perform energy performance simulations [11][12][13][14][15].…”
Section: Software and Analysismentioning
confidence: 99%
“…Al-Shargabi et al [21] stressed the importance of characteristics such as WWR and wall U-value as key factors that affect energy consumption, as low insulation performance is typical for glass used in windows compared to other construction materials [22]. Nadeem et al [23] drew attention to the correlation between WWR and wall insulation with the conclusion that the rise in WWR value leads to a decrease in annual energy use in uninsulated constructions.…”
Section: Introductionmentioning
confidence: 99%
“…La Fleur et al [46] used a BEM model created in IDA ICE version 4.6.2 and concluded that energy demand can be reduced by 44% after renovation. Nadeem et al [23] applied EnergyPlus to carry out energy simulations for a reference house in different climate conditions. Other examples of software appropriate for physical models include eQuest [5], EnergyPlus, BEopt v.2.8.0.0 [10], WUFI Plus v.3.2.0.1 [47], and Ecotect [48].…”
Section: Introductionmentioning
confidence: 99%